PENDAMPINGAN MASYARAKAT KAMPUNG OLAHAN HASIL TAMBAK BERBASIS JARINGAN KOMUNIKASI (KAJIAN EKONOMI MASYARAKAT KELURAHAN KALIANYAR, BANGIL, PASURUAN) - Muhammad Hermansyah (LPPM Universitas Yudharta Pasuruan, 2018)
Community assistance is intended as an approach method to learn about the conditions and lives of the assisted areas from, with, and by the target communities themselves, including also the activities of studying, planning and acting and evaluating the activities carried out. The purpose of this study is primarily to create a model of community empowerment, by developing the ability of the community to assess their own circumstances according to planning and action, the community by being involved directly in the planning and implementation stages of development, using assessment tools and stages. The method used in this study emphasizes the ability of Participatory Rural Appraisal (PRA) techniques, namely in the participation of data collection, the use of study tools and the principle of independence. The emphasis is precisely on the process of community learning and practical objectives for program development and encouraging communities to participate in improving and reviewing their knowledge of economic life, so that they can develop plans and actions through the stages of preparation, implementation of field activities and evaluation monitoring. The results of the study show that the implementation of community activities carried out in a participatory manner by building a network of communication in economic activities is able to stimulate the progression and growth of creative SMEs in the Processed Village of Kalianyar Pond Products with an estimated